Meigs Syndrome, Pseudo-meigs Syndrome, Or Pseudo-pseudo Meigs Syndrome? A Case Report - Azie Jumaatul Adawiyah Nabir; Lau Chiew Yee; Adilah W. Ab Rahim; Aliyyah Mohammad Khuzaini (Elsevier, 2024)
Indexed by Scopus